Psychophysical Interactions with Entangled Photons: Five Exploratory Studies - Radin, Dean; Bancel, Peter A.; Delorme, Arnaud (Journal of Anomalous Experience and Cognition, 2021)
Objective: Four laboratory studies and an online experiment explored psychophysical (mind-matter) interactions with quantum entangled photons. Method: Entanglement correlation strength measured in real-time was presented via a graph or dynamic images displayed on a computer monitor or web browser. Participants were tasked with mentally influencing that metric. Results: A statistically significant increase in entanglement strength was obtained in experimental conditions in the four lab studies (p < 0.02), with particularly strong results observed in three studies conducted at the Institute of Noetic Sciences (p < 0.0002). Modest results (p < 0.05) were observed in a high-quality subset of entanglement samples in an online experiment. Control experiments using the same equipment and protocols, but without observers present, showed results consistent with chance expectation in both the lab and online studies. Conclusion: These outcomes suggest that the fidelity of entangled states and the nonlocal resource they entail may be mutable in systems that include conscious awareness. This is potentially of interest for quantum information technologies such as quantum computation, encryption, key distribution, and teleportation. The results are also relevant for interpretations of quantum theory, especially if future studies show that entanglement strength can be mentally modulated above the Tsirelson Bound – the upper limit predicted by quantum theory. Such an outcome would suggest that quantum theory in its present form does not hold when physical systems interact with certain mental states. The results of these exploratory experiments justify continued investigation of entangled photons as targets of mind-matter interaction.